Cho P= ($\frac{2+\sqrt{x}}{2-\sqrt{x}}$ – $\frac{2-\sqrt{x}}{2+\sqrt{x}}$ – $\frac{4x}{x-4}$ ) : $\frac{\sqrt{x}-3}{2\sqrt{x}-x}$ a)Rút gọn b)Tìm x để

Question

Cho P= ($\frac{2+\sqrt{x}}{2-\sqrt{x}}$ – $\frac{2-\sqrt{x}}{2+\sqrt{x}}$ – $\frac{4x}{x-4}$ ) : $\frac{\sqrt{x}-3}{2\sqrt{x}-x}$
a)Rút gọn
b)Tìm x để \P\ =1

in progress 0
Delilah 3 tuần 2021-08-21T17:12:19+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-21T17:13:23+00:00

    CHÚC BẠN HỌC TỐT!!! 

    Giải thích các bước giải:

     

    0
    2021-08-21T17:13:36+00:00

    Giải thích các bước giải:

    a,

    ĐKXĐ: \(\left\{ \begin{array}{l}
    x > 0\\
    x \ne 4\\
    x \ne 9
    \end{array} \right.\)

    Ta có:

    \(\begin{array}{l}
    P = \left( {\dfrac{{2 + \sqrt x }}{{2 – \sqrt x }} – \dfrac{{2 – \sqrt x }}{{2 + \sqrt x }} – \dfrac{{4x}}{{x – 4}}} \right):\dfrac{{\sqrt x  – 3}}{{2\sqrt x  – x}}\\
     = \left( {\dfrac{{2 + \sqrt x }}{{2 – \sqrt x }} – \dfrac{{2 – \sqrt x }}{{2 + \sqrt x }} – \dfrac{{4x}}{{\left( {\sqrt x  – 2} \right)\left( {\sqrt x  + 2} \right)}}} \right):\dfrac{{\sqrt x  – 3}}{{\sqrt x .\left( {2 – \sqrt x } \right)}}\\
     = \dfrac{{{{\left( {2 + \sqrt x } \right)}^2} – {{\left( {2 – \sqrt x } \right)}^2} + 4x}}{{\left( {2 – \sqrt x } \right)\left( {2 + \sqrt x } \right)}}:\dfrac{{\sqrt x  – 3}}{{\sqrt x .\left( {2 – \sqrt x } \right)}}\\
     = \dfrac{{\left( {x + 4\sqrt x  + 4} \right) – \left( {x – 4\sqrt x  + 4} \right) + 4x}}{{\left( {2 – \sqrt x } \right).\left( {2 + \sqrt x } \right)}}.\dfrac{{\sqrt x .\left( {2 – \sqrt x } \right)}}{{\sqrt x  – 3}}\\
     = \dfrac{{4x + 8\sqrt x }}{{\left( {2 – \sqrt x } \right)\left( {2 + \sqrt x } \right)}}.\dfrac{{\sqrt x .\left( {2 – \sqrt x } \right)}}{{\sqrt x  – 3}}\\
     = \dfrac{{4\sqrt x \left( {\sqrt x  + 2} \right)}}{{2 + \sqrt x }}.\dfrac{{\sqrt x }}{{\sqrt x  – 3}}\\
     = \dfrac{{4\sqrt x .\sqrt x }}{{\sqrt x  – 3}}\\
     = \dfrac{{4x}}{{\sqrt x  – 3}}\\
    b,\\
    \left| P \right| = 1 \Leftrightarrow \left[ \begin{array}{l}
    P = 1\\
    P =  – 1
    \end{array} \right.\\
    TH1:\,\,\,P = 1 \Leftrightarrow \dfrac{{4x}}{{\sqrt x  – 3}} = 1\\
     \Leftrightarrow 4x = \sqrt x  – 3\\
     \Leftrightarrow 4x – \sqrt x  + 3 = 0\\
     \Leftrightarrow {\left( {2\sqrt x } \right)^2} – 2.2\sqrt x .\dfrac{1}{4} + \dfrac{1}{{16}} + \dfrac{{47}}{{16}} = 0\\
     \Leftrightarrow {\left( {2\sqrt x  – \dfrac{1}{4}} \right)^2} + \dfrac{{47}}{{16}} = 0\,\,\,\,\,\left( {vn} \right)\\
    TH2:\,\,\,P =  – 1 \Leftrightarrow \dfrac{{4x}}{{\sqrt x  – 3}} =  – 1\\
     \Leftrightarrow 4x =  – \sqrt x  + 3\\
     \Leftrightarrow 4x + \sqrt x  – 3 = 0\\
     \Leftrightarrow \left( {\sqrt x  + 1} \right)\left( {4\sqrt x  – 3} \right) = 0\\
     \Leftrightarrow \left[ \begin{array}{l}
    \sqrt x  =  – 1\\
    \sqrt x  = \dfrac{3}{4}
    \end{array} \right. \Leftrightarrow \sqrt x  = \dfrac{3}{4} \Leftrightarrow x = \dfrac{9}{{16}}
    \end{array}\)

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )